Obywatelstwo i narodowość w językowym obrazie świata młodzieży - Hau, Anna; Wądołowska-Lesner, Katarzyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
In the undertaken study, the understanding of the concepts of citizenship and nationality by the Polish young people, I assume that these categories are essential in terms of shaping the national identity of the individual. The system of concepts that define the personality of a human, the ability to reflect on their content, correctness, common connection, allows individuals to unite into a certain community. Thus, the analysis of linguistic ways of describing non-linguistic reality is also associated with the description of the mental representations of the individual, and therefore the ways – in cognitive processes – to relate to the world, to make an image of the world, to create knowledge about the world.